The Romanian Traditional Shirt Ia: Agency, Complexity, and Thing-Power in an Immigrant Teacher Identity Journey - Enache, Mihaela (Art/Research International, 2026)
Through critical collaborative autoethnography with arts-based methods, I experienced the embodied making of a Romanian traditional shirt called ia, as a practical exploration of my immigrant teacher identity. Ia changed my world; she became an intrinsic part of my identity and the core of my study. She deserved attention and representation because she was a presence. I thus responded to a provocation: not only did I understand the object/subject/agent of my study differently, but I became different myself and transformed my relationships with humans and nonhumans. Ia changed from an object into a subject and a participant; she became a storyteller and my teacher. Through complexity, thing-power, and agency, ia generated an extensive theoretical framework and enabled juxtapositions of concepts from Romanian village metaphysics, new materialism, and quantum entanglements.